Demulsifier Performance Study: Relationship between Demulsifier Properties with Crude Characteristics - Manjit Singh, Amritpal Kaur; Majnis, Mohd Fadhil; Halim, Nor Hadhirah; Abdallah Mohammed, Elhassan Mostafa (International Journal of Integrated Engineering, 2024)
Due to the vast range of different types of crude oil characteristics which differ from region to region, wells and even day to day, developing and selecting effective demulsifiers for regional crude oils has been a time-consuming and tedious process. This experimental study was performed to define a relationship between crude characteristics of wax, asphaltene and crude API with relative solubility number (RSN) properties and chemistry groups of demulsifiers with their performances accordingly. Twenty-five different types of demulsifiers with RSN ranging from ten to twenty-three were tested using demulsifier bottle test. The demulsifiers comprise resin alkoxylate, modified polyol and polyimine derivative. Synthetic crude is used throughout the study with API of 27, 34 and 40. The wax and asphaltene contents of each crude API are varied. The study used 2% NaCl water representing the average salinity of the produced water in Malaysian offshore fields. Demulsification test was conducted using a 50:50 ratio in terms of the crude and brine volume.100 ppm demulsifier dosed into emulsion mixture, and the separation was monitored and recorded after 30 minutes. The demulsifier bottle test is performed at 60 oC, similar to the operating temperature of demulsifier injection in Malaysia offshore field. Based on the three chemistry groups, resin alkoxylate showed the best performance, while polyimine derivative-based demulsifiers had the poorest performance. The demulsifier with high RSN, which is from 19 to 23, works best in resolving the emulsion compared to the low RSN demulsifiers.